2001
DOI: 10.1097/00000658-200109000-00012
|View full text |Cite
|
Sign up to set email alerts
|

A 10-Year Experience of Liver Transplantation for Hepatitis C: Analysis of Factors Determining Outcome in Over 500 Patients

Abstract: ObjectiveTo determine the factors affecting the outcome of orthotopic liver transplantation (OLT) for end-stage liver disease caused by hepatitis C virus (HCV) and to identify models that predict patient and graft survival. Summary Background DataThe national epidemic of HCV infection has become the leading cause of hepatic failure that requires OLT. Rapidly increasing demands for OLT and depleted donor organ pools mandate appropriate selection of patients and donors. Such selection should be guided by a bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
189
6
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(209 citation statements)
references
References 40 publications
(37 reference statements)
11
189
6
3
Order By: Relevance
“…[13][14][15]29,30 However, in 1997, Markmann et al 15 published single-center data and reported survival rates of 52% at 1 year and 42% at 5 years in adults undergoing re-OLT between 1984 and 1996. In comparison, we show survival rates of 67% at 1 year and 52% at 5 years in adults undergoing re-OLT between 1996 and 2002.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15]29,30 However, in 1997, Markmann et al 15 published single-center data and reported survival rates of 52% at 1 year and 42% at 5 years in adults undergoing re-OLT between 1984 and 1996. In comparison, we show survival rates of 67% at 1 year and 52% at 5 years in adults undergoing re-OLT between 1996 and 2002.…”
Section: Discussionmentioning
confidence: 99%
“…Through randomized, blinded fashion we matched each case with its corresponding control based on specific characteristics that previous studies have demonstrated to most likely influence clinical outcomes. 18,21 In order of importance, these variables included donor age (within 10 yr), year of transplantation (within 4 yr), United Network for Organ Sharing/Model for End-Stage Liver Disease score, and recipient age (within 20 yr). Donor age has shown to impact survival after liver transplantation in HCV and thus was chosen as a matching variable.…”
Section: Matched Analysismentioning
confidence: 99%
“…6 The University of California at Los Angeles (UCLA) group noted the median time to recurrence was 34 months posttransplantation, with 68% having recurrent hepatitis at 5-year follow-up. 9 A recent study has evaluated the histologic changes in patients in whom cirrhosis developed after transplantation. 10 Eighty percent of these patients had recurrent disease within 6 months.…”
Section: Natural History Of Hcv Posttransplantationmentioning
confidence: 99%
“…Of concern, Ghobrial and others reported death risk ratios of 12.4, 4.2, 5.5, and 1.7 in patients who had HCV recurrence within the first 12, 12 to 24, 24 to 36, and more than 36 months after transplantation. 9 Interestingly, many studies note that hepatitis C patients compared with controls have not shown a reduced graft or patient survival. [11][12][13] Recently, Forman et al, using the data from UNOS, reported that HCV-positive recipients were associated with an increased rate of death (hazard ratio, 1.23), especially in female recipients, compared with non-HCV recipients.…”
Section: Natural History Of Hcv Posttransplantationmentioning
confidence: 99%